A new fatigue model including thermal ageing for low copper aluminum-silicon alloys. (2018) - BERANGER, M.; FIARD, J.M.; AMMAR, K.; CAILLETAUD, G.
Abstract: Numerical simulation is more and more used in automotive industry to reduce design time and cost. Moreover, for high performance engines, the development of cylinder heads requires well known and adapted materials to ensure their reliability. The estimation of adapted fatigue criteria based on few experiments is thus an important challenge: to obtain more predictive model on more complex mechanical phenomena. This paper describes the methodology adopted by Renault to estimate fatigue life of a new aluminum-silicon alloy. A low copper aluminum-silicon alloy has been developed for a new generation of cylinder heads. Those kinds of alloys provide a good compromise between the two main failure modes encountered for cylinder heads: high cycle fatigue of water jacket and low cycle fatigue of fire deck. However, those materials are subjected to thermal ageing that can affect mechanical behavior, such as yield stress and hardening, but also fatigue mechanisms at higher temperatures. This article presents first the selected constitutive equations that introduce thermal ageing effect in a cyclic elasto-viscoplastic model. The low cycle fatigue criterion is then calibrated on the relevant database, which includes isothermal and non-isothermal tests. The fatigue criterion is a specific version of a classical model previously developed at Onera. The critical variables for the fatigue part are the stress amplitude and the mean stress, both of them being normalized by an ultimate stress which depends on temperature and ageing state. Finally, the constitutive and damage models have been applied on 3D cylinder head numerical analysis. The paper proposes a brief comparison of those results with more classical simulations made on cylinder heads and highlights the perspectives offered by this new aluminum-silicon alloy.